ANALISIS AJARAN KITAB DANIEL PASAL 4 PENGAKUAN RAJA NEBUKADNEZAR TENTANG KUASA ALLAH DANIEL - Nainggolan, Bartolomeus Diaz (Fakultas Filsafat Universitas Advent Indonesia, 2019)
Overcoming pride and being humble is a desire that cannot be achieved throughhumanitarian conditions. Humility is a goal that is difficult to understand. When youthink you have it when it also disappears. But God can give power to overcome prideand live humility. God can turn every temptation of pride into an opportunity to givethanks.